HUMAN RIGHTS COMMISSION AND ITS EFFECTIVE ROLE IN INDIA - S. Muniaselvi; K. Sasikala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Human Rights originate with the birth of the individuals and are essential for the adequate development of human personality and their progress and happiness. A number of Declarations, Covenants and Legislations have been imitated and entered into the National and International levels for the effective promotion and protection of Human Rights. However the violation of Human Rights has been increasing day by day. Hence Human Rights enforcement mechanism has been established to enforce Human Rights at the national and International levels. Today, there is a need of strong society based on the fundamental principles of acceptance of Human Rights both in theory as well as in practice. States play a very important role in the promotion and protection of Human Rights. The Philosophy of Human Rights and Fundamental Freedoms were incorporated in the Constitution in the Preamble and in the chapters of Fundamental Rights and Directive Principles of State Policy. The Supreme Court of India and state High Courts have broad powers under the Constitution to enforce Fundamental Rights. This paper is an endeavour to focus upon the functioning of the human rights commission of India in protecting the rights violations.